Effect of Completion of Judgments on Finalization and Enforcement of Judgments in Civil Procedure Law - Zeynep Bahadır (İstanbul Hukuk Mecmuası)
Article 305/A of the Code of Civil Procedure (Law No. 6100) was enacted pursuant to the Law on Amending the Code of Civil Procedure and Other Laws (Law No. 7251), and the institution of “completion of judgments” was introduced into our legal system. According to the article, “within one month from the notification of the judgment, each party may request a supplementary ruling from the court for matters left undecided partly or as a whole, even though they were asserted or ought to be resolved ex officio. Appellate remedies are available against these rulings.” Although this article, which allows the court to supplement its previous judgment, is completely new to the civil judiciary, it is actually an adaptation of article 437/4 of the Code of Civil Procedure, which allows this procedure in arbitration. Through completion of judgments, a supplementary ruling may be requested from the court to avert any omission in the judgment if a claim in accumulation was left unresolved or if such judicial costs as the attorney’s fee were not decided upon. This legislation serves the principle of procedural economy and the realization of a more effective legal protection. However, because completion of judgments is a brand-new institution in the civil judiciary with an ambiguous nature, several problems must be addressed. These problems can be classified into two categories: the possibility of contradictory judgments due to separate appellate remedies for both rulings, and the question of whether these judgments may be executed separately and, if so, whether they may be joined in the enforcement procedure. This paper examines these issues and presents possible solutions.